Pengaruh Kualitas Layanan, Persepsi Harga, dan Word of Mouth terhadap Minat Beli Ulang dengan Kepuasan Konsumen Muslim sebagai Pemediasi - Ardiyansyah, Muhammad; Abadi, Muhammad Taufiq (Universitas Bunda Mulia, 2023)
This study aims to provide an empirical explanation of the effect of service quality, price perceptions and word of mouth on repurchase intention through Muslim consumer satisfaction as an intervening variable. The type of research in this research is survey research with quantitative methods used. With a sample of 97 respondents, Muslim consumers of Pondok Makan Sambal Djawa were determined by using incidental sampling technique. Researchers used a questionnaire as an instrument to obtain data. Data were analyzed using SPSS 25 in the form of path analysis, the results showed that service quality and word of mouth had a positive and significant effect on Muslim consumer satisfaction, price perceptions had no effect on Muslim consumer satisfaction, word of mouth and Muslim customer satisfaction had a positive and significant effect on interest repurchase, service quality and perceived price have no effect on repurchase intention and Muslim consumer satisfaction mediates between the effect of service quality and word of mouth on repurchase intention, and Muslim consumer satisfaction does not mediate between the effect of perceived price on Muslim consumer repurchase intention